Legal Responsibility for Medical Risks and Medical Negligence in The View of Health Law - Sidi, Redyanto (Journal of General Education Science, 2023)
This research examines legal aspects related to medical risk and negligence in the context of health law in Indonesia, especially after the ratification of Law Number 17 of 2023 concerning Health. Normative research methods are used, with a focus on examining legal principles, statutory regulations, relevant cases, and conceptual approaches in legal science related to medical negligence. The research results highlight that in criminal law, liability for medical acts deemed negligent depends on clear evidence of fault, in accordance with the principle "No punishment if there is no fault". This law specifically regulates criminal sanctions for health workers who are proven to have committed negligence that causes serious injury or death to patients, as regulated in Article 440. Medical risk is an inherent part of the practice of medicine, but medical negligence is defined as a deviation from the expected standard of care. This research also highlights the obligations of hospitals in providing safe and effective services in accordance with established standards, and their accountability for negligence that occurs, as regulated in Articles 189 and 193. Law Number 17 of 2023 also introduces a risk management system to prevent medical negligence, as well as the formation of a special assembly by the Minister of Health to resolve medical disputes, including allegations of negligence. This research underlines the importance of a comprehensive understanding of health law in medical practice and handling of medical negligence cases in Indonesia.